2013
DOI: 10.1213/ane.0b013e31826f0622
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Sparing Effect of Preemptive Bolus Low-Dose Ketamine for Moderate Sedation in Opioid Abusers Undergoing Extracorporeal Shock Wave Lithotripsy

Abstract: Preemptive low-dose ketamine (0.1 mg/kg) as a bolus has opioid-sparing effects in opioid abusers undergoing moderate sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…A pre-emptive bolus dose of ketamine (0.1 mg/kg) has opioid-sparing effects in opioid abusers undergoing moderate sedation [33] . A study of intrinsic functional brain connectivity in twelve healthy volunteers, through resting state functional magnetic resonance imaging, found obvious changes in certain regions of the central nervous system (ie, the amygdala, insula, and anterior cingulate cortex), which could explain ketamine's pharmacodynamic profile with respect to analgesia and its psychedelic side effects [34] .…”
Section: Wwwchinapharcom Gao M Et Almentioning
confidence: 99%
“…A pre-emptive bolus dose of ketamine (0.1 mg/kg) has opioid-sparing effects in opioid abusers undergoing moderate sedation [33] . A study of intrinsic functional brain connectivity in twelve healthy volunteers, through resting state functional magnetic resonance imaging, found obvious changes in certain regions of the central nervous system (ie, the amygdala, insula, and anterior cingulate cortex), which could explain ketamine's pharmacodynamic profile with respect to analgesia and its psychedelic side effects [34] .…”
Section: Wwwchinapharcom Gao M Et Almentioning
confidence: 99%
“…To overcome inflammatory responses, different drugs are being tried by the technique. These trials cover NSAIDs, opioids, NMDA receptor antagonists and systemic antiepileptics25262728. Stephens et al .…”
Section: Discussionmentioning
confidence: 99%
“…As ketamine provides early knee mobilization, it has been reported as a useful adjuvant for perioperative multimodal analgesia in patients undergoing arthroplasty (17). Another randomized, placebocontrolled study stated the opioid-sparing effect of preemptive IV bolus ketamine (18). On the other hand, Lopez-Alvarez et al (19) indicated that morphine consumption and postoperative pain scores were higher in the group in which ketamine was administered.…”
Section: Discussionmentioning
confidence: 99%